The Role of AI in Enhancing Agricultural Labor Efficiency: Perspectives from HR Managers in Agri-Tech Firms - Septien Dwi Savandha; Ade Fitria Fatimah; Rani Santika; Komarudin (Digital Agriculture and Innovation Journal, 2025)
Artificial intelligence (AI) 's rapid adoption in agriculture transforms labor efficiency, especially in agri-tech firms. This study explores the role of AI in enhancing labor productivity from the perspectives of human resource (HR) managers in the sector. The primary objective is to understand how AI technologies influence labor allocation, management practices, and workforce adaptation. Utilizing a qualitative research methodology, data were collected through semi-structured interviews with HR managers in agri-tech firms. Thematic analysis was applied to interpret the data, highlighting key trends in AI implementation. Results show that AI significantly reduces manual labor in repetitive tasks like crop monitoring and irrigation, allowing firms to reallocate human resources to higher-value roles. However, challenges such as employee resistance, skill gaps, and high implementation costs were also reported. HR strategies, including phased AI implementation and extensive training programs, have effectively managed workforce transitions. The study concludes that AI is vital for improving labor efficiency in agriculture, but its full potential requires careful management of human resources to mitigate resistance and enhance technical proficiency. These findings offer practical implications for HR managers and policymakers aiming to integrate AI sustainably into agricultural labor practices